Collective citizenship: From citizenship and mental health to citizenship and solidarity. (6th November 2019) - Quinn, Neil; Bromage, Billy; Rowe, Michael
Abstract: Although the concept of citizenship is a widely used theoretical framework within political philosophy, its use in the field of mental health remains underexplored. Within this context, citizenship emphasises the social inclusion and participation of people who are marginalized and offers a more social and relational view of services and support for people with mental health problems than has been common in mental health systems of care. At the same time, however, the citizenship approach has operated in the context of systems of care in the United States that favour highly individualized conceptions of, and approaches to, care, and these systems of care operate in the social and political context of highly individualized concepts of the citizen. In this article building on the work of other citizenship scholars, we argue that a collective form of citizenship, grounded in the 5Rs framework, holds the individual and collective in creative tension. Furthermore, the paper applies this model to the domain of mental health, where people are treated in individualistic ways and experience marginalisation, making the collective dimension imperative and promoting participation, empowerment and the contribution for social change to people with mental health problems. Our theoretical framework of collective citizenship, while geared toward the needs of persons with mental health problems, also contributes to recent citizenship theory on the inclusion of marginalized, stigmatised, and excluded groups. We illustrate the application of this approach through an ethnographic‐participant observation case study of a collective citizenship group with which we are associated.